Development of Employees Attendance Features of Human Resource Information System in A National Logistics Company - Setiowati, Rini; Yuniarti Utami, Eva; Sonani, Nia; Sudrajat, Angga Pramadista; Hery Santoso, Muhammad (SEULANGA SYSTEM PUBLISHER, 2023)
The purpose of this study is to determine how to create an HRIS application. The following steps make up the data collection approach used in the development of this application: observation, interviews, and literature review. The author develops systems using the Requirements Analysis and Design (RAD) method, which comprises three stages: requirement planning, design workshop, and implementation (application). The author has presented research and authors from which the following conclusions can be made: Using UML (Unified Modeling Language) tools and the RAD (Rapid Application Development) methodology, the HRIS attendance information system was evaluated and designed. through the use of three stages for the design, implementation, and requirements planning processes. Through the attendance function in the developed HRIS (Human Resources Information System) application, the system development can facilitate data processing and employee absence reporting for HR (Human Resources). Obviously, there are still issues with this method. Numerous things can still be done to improve and further expand this system. It is envisaged that development will extend beyond attendance and include the ability to use the HRIS application to distribute information on HRD activities.